Communication from the Adjutant General in response to a resolution of the Senate : January 19, 1861 (Document (Virginia. General Assembly. Senate), 1861)
January 19, 1861 Adjutant General's response to a Senate resolution of January 14th, noting the number of commissioned cavalry troops and revolvers in service.